Characterization of Aluminum Matrix Metal Composite Hybrid Reinforced With SiCw/(Al2O3-Mg) on Thermal Conductivity and Hardness - Suarsana, Ketut; Soenoko, Rudy; Negara, DNK Putra; Sunu, P.W. (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2021)
Characteristics of composite materials that are light, strong, heat resistant, and high hardness are needed in their application. This study aims to obtain a hard material and good heat conductivity, with the innovation of making aluminum matrix composites (AMC) from aluminum powder as a matrix, combined with silicon-carbon whisker (SiCw) and alumina particles (Al2O3p), and adding Magnesium through the powder process metallurgy. The method of making composites was carried out by means of powder metallurgy. The research variables composition I, II, and II with Al/(SiCw+Al2O3/Mg), were given temperature treatment: 500, 550, and 600oC. The test results show that there is an increase in the mechanical properties of the composites both from variations in composition and also from variations in treatment temperature because the bond resulting from the addition of Al2O3 reinforcement has hard and fine grain properties. The physical and mechanical properties of the test results are in the form of the highest density at composition I, 600oC (2,699 gr/cm3) while the hardness at composition III is 600oC (42,438 HV) and heat conductivity at composition III, 600oC (185,183 Watt/m.oC). Scanning with SEM showed that the pore size decreased from the treatment temperature of 500oC to 600oC due to phase changes and a stronger bond between the matrix and the reinforcement. So that the influence of composition and temperature will affect the thermal conductivity, hardness, and density of the composites.